Hyper-Personalization Marketing and Consumer Purchase Behavior in Indonesia: The Role of Culture - Tifani Dame Hasany; Dhanny Safitri; Dinis Cahyaningrum; Isra Dewi Kuntary Ibrahim; Ni Wayan Adelia Mutiara Asri (Laboratorium Riset Ekonomi, 2026)
The rapid advancement of artificial intelligence (AI), big data analytics, and digital technologies has transformed marketing practices by enabling businesses to implement hyper-personalization strategies that deliver individualized customer experiences. This literature review examines the relationship between hyper-personalization marketing and consumer purchase behavior within the Indonesian context, with particular emphasis on the moderating role of culture. Drawing on the Technology Acceptance Model (TAM), the Stimulus–Organism–Response (SOR) framework, Relationship Marketing Theory, and Hofstede's Cultural Dimensions Theory, the review synthesizes existing literature on personalized marketing, consumer behavior, and cultural influences. The findings suggest that hyper-personalization generally enhances consumer purchase behavior by improving perceived relevance, trust, customer experience, and engagement. However, its effectiveness is influenced by Indonesia's cultural characteristics, particularly collectivism, power distance, and the importance of social influence and trust in purchasing decisions. The review also identifies a lack of empirical research integrating hyper-personalization, consumer purchase behavior, and cultural factors in Indonesia. By synthesizing existing knowledge, this study provides a theoretical foundation for future research and offers insights for businesses seeking to develop culturally appropriate AI-driven marketing strategies.